Nutzung multikriterieller und unscharfer (FUZZY-)Analysen zum Talentscreening im Sport - Ester, J.; Zinner, J.; Utesch, T.; Büsch, D. (Informatik-Spektrum, 2020)
In sports, motor assessments are often used in the context of talent screening. They consist of different motor skills as well as other relevant person parameters. Standard evaluation methods usually rely on the classification of the results mostly in five-point performance categories. Especially in large samples, however, procedures are needed that are able to provide reliable differentiations within the "best group" and the "worst group". The solution, e.g., in the project BERLIN HAT TALENT, is the usage of multicriteria and fuzzy mathematical theories and methods. In this approach, subjective theories and knowledge of coaches, teachers and sports scientists can be explicitly integrated in the decision process. This is realized by discursive validations and the construction of evaluation functions, which can also be interpreted as so-called membership functions for fuzzy sets. The added value of the presented multi-attributive decision models is the possibility to integrate expert knowledge. Finally, the models are illustrated within an interactive software.